OPTIMASI PERENCANAAN PRODUKSI DENGAN MENGGUNAKAN METODE LINEAR PROGRAMMING PADA CV. ACEH BAKERY - Ria Asysyfa Hasmi (Universitas Teuku Umar, 2015)
One purpose is to review company get advantages The Maximum and minimum cover charge thing. Many HAL should be made for a review of A Company Posted achieve these objectives, ie only prayer is how to determine Products Should TYPE WITH generated utilizing existing resources thus able to contribute Maximum AGRO. Company Must Develop CAN BE Meticulously Term Planning Production will be produced for review optimize profits WITH take into account factors such as the production of raw materials. When Paid Products produced too big Namely State exceeds the demand limit, then HAL husband will result in inaccuracies allocate factors of production is owned, thereby increasing the cost of production includes. Here Writers Wanted Looking for an alternative solution to a review AS WITH planned increase profits Production WITH progamming optimal linear method.The findings of The TIN using software TORA BY TYPE findings For green bread, CV. Aceh Bakery Must be producing as much as 152 packs / day. For TYPE bread Skinless, CV. Aceh Bakery Must be producing as much as 149 packs / day. For TYPE crusted bread, CV. Aceh Bakery Must be producing 150 packs / day. Article Search Google so, then CV. Aceh Bakery will get a profit of Rp.1.973.100, - / day.Keyword : Roti, Optimization, Linier Proggramming, TORA.